EIB Working Paper 2024/01 - Dynamics of productive investment and gaps between the United States and EU countries - European Investment Bank (European Investment Bank, 2024)
After the global financial crisis, investment fell more substantially than it had in the wake of previous recessions. With investment seemingly recovering faster in the United States than in Europe, the fear of a lasting gap emerged in Europe. This detailed analysis compares the investment dynamics and capital accumulation in the United States and the European Union, focusing on 2013-2019. It uses data from Eurostat and EU KLEMS releases to highlight the gaps and variations in investment strategies across different countries and asset types. The working paper provides key insights into the investment rates, growth of real gross fixed capital formation, and accumulation of stocks. It reveals an investment gap primarily due to lower rates in tangible information and communication technology and intangible assets after the global financial crisis, particularly in larger EU Member States. In addition, the report provides an in-depth analysis of diverse asset types and their role in the investment dynamics. It uncovers the European Union’s strength in construction assets and its persistent gaps in information and communications technology and intangible assets, indicating a need to increase investments in these areas. Furthermore, the analysis discloses the heterogeneity within the European Union, with countries like Ireland, Czech Republic, and Sweden leading in investment rates, while others, including the Netherlands, Germany, Italy, and Spain, falling behind. This working paper is a tool for understanding the nuances of global investment trends and for formulating effective strategies to address identified gaps. It offers guidance and insights for policymakers, investors, and businesses operating in the global economic environment.